2005
DOI: 10.1136/bjsm.2004.016410
|View full text |Cite
|
Sign up to set email alerts
|

High reproducibility of patellar tendon vascularity assessed by colour Doppler ultrasonography: a reliable measurement tool for quantifying tendon pathology

Abstract: Background: This study examined whether patellar tendon vascularity could be quantified accurately in the clinical setting using colour Doppler ultrasonography. Methods: A sonographer and two radiologists visually estimated tendon vascularity in millimetres in 74 tendons during ultrasound (US) examination and from hard copy films. These estimates were then compared to the length of vessels measured from the digital image in millimetres and the correlation between them was determined. A subset of 16 tendons was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 8 publications
0
47
0
Order By: Relevance
“…Runners with VISA-A scores less than 80 were also considered symptomatic [20]. The B-mode US (hypoechogenicities) and SE changes that were evident in both the longitudinal and transverse planes (with dimension measured more than 1 mm in either planes) were documented and graded according to previously validated criteria listed in Table 1 [14,21,22]. Grades 2 and 3 were defined as pathologic tendons for all imaging modes.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Runners with VISA-A scores less than 80 were also considered symptomatic [20]. The B-mode US (hypoechogenicities) and SE changes that were evident in both the longitudinal and transverse planes (with dimension measured more than 1 mm in either planes) were documented and graded according to previously validated criteria listed in Table 1 [14,21,22]. Grades 2 and 3 were defined as pathologic tendons for all imaging modes.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…With power or colour Doppler, areas with increased blood flow may be found, and the amount of colour may be quantified 19 23 24. This is used in disorders where hyperaemia is an integral part of the condition—arthritis, bursitis, epicondylitis and tendonitis.…”
mentioning
confidence: 99%
“…Abnormal blood flow can be observed in several clinical situations [27,28]. Some studies have shown that intratendinous flow is associated with symptomatic patellar and Achilles tendinopathy, which supports monitoring tendon neovascularization as a diagnostic indicator of critical situations [5]. To our knowledge, this study is the first to utilize ultrasound evaluation of blood flow in the IFP, although the exact mechanism underlying the increased blood flow requires further investigation.…”
Section: Discussionmentioning
confidence: 85%